Easy Guide to Long Essay/Dissertation Writing - Nyantakyi-Baah, Lydia (UniMAC-GIJ, 2020)
The guidelines and examples in this handbook reflect a long essay or a thesis that has five chapters. The purpose of this handbook is to serve as a guide for both undergraduate and postgraduate students when writing their research work. It covers tips on how to select a research topic and write a proposal, general guidelines and layout of the various chapters, that is, chapters one to five and the preliminary pages, abstracting, online searches and information sources that can be useful for literature review. Some examples have been provided in this handbook.
Handbook
Keywords: Guide, Research Writing, Ghana, University Education